A literature review of netizens' online public opinion dissemination behavior on food safety - Li, Xiaopei; Talib, Zunirah Mohd (Edelweiss Applied Science and Technology, 2025)
This paper reviews the current status of research on the dissemination behavior of Chinese netizens regarding food safety in recent years. It identifies the progress made and existing problems, providing practical guidance for relevant authorities to develop targeted governance strategies. This is of significant importance for optimizing the public opinion governance system related to food safety. A systematic review methodology was employed to organize recent research findings, with in-depth analysis conducted across several dimensions, including the theoretical framework, influencing factors, dissemination pathways, and the characteristics of netizens' public opinion dissemination behavior concerning food safety. The dissemination behavior of netizens is driven by multiple factors such as the credibility of information, emotional appeal, and social trust. The dissemination pathways exhibit features of fragmentation, circle-based sharing, and cross-platform dissemination. Future research should focus on understanding the influence mechanisms of emerging platforms, the dynamic evolution of netizens' psychology, and the integration of interdisciplinary theories. These efforts will help establish a solid foundation for enhancing the public opinion governance system related to food safety.